Effect of diameter, twist angle, and blade count on the thermal-hydraulic performance of a decaying twisted swirler - At-Tasneem, Mohd Amin; Wan Azmi, Wan Hamzah; Mohd Azmi, Ismail (Elsevier, 2023)
Inserting a decaying swirler into a heat exchanger has been shown to improve heat transfer with minimal effect on the friction factor. The study analyses the effect of diameter, twist angle, and blade count on the thermal-hydraulic performance of a Decaying Twisted Swirler (DTS) in a horizontally heated tube. The diameter, twist angle, and DTS's blade count are examined for 13.5 mm–15.5 mm with a 0.5 mm interval, 0°–360° with a 60° gap, and 2 to 6 blades, respectively. The Nusselt number, friction factor, and thermal-hydraulic performance are examined for Reynolds numbers between 4583 and 35000. The relative Nusselt number and friction factor increase as DTS diameter and twist angle increase, reaching a maximum value at Re = 4583. Despite this, the relative Nusselt number dispersed as the blade count increased. The relative friction factor increases as the blade count increases. Maximum relative Nusselt number and friction factor reached 1.64 and 3.25, respectively with DTS's 15.5 mm diameter, 360° angle, and 4 blades. Nonetheless, the thermal-hydraulic performance is greatest when the DTS has a diameter of 15.5 mm, a twist angle of 180°, and 2 blades with 1.17.